(untitled) (Development Service Industry Management, 2023)
The article pays attention to issues of the policy of managing the development of tourist enterprises and the use of marketing tools for such purposes, in particular, its product policy. The purpose of the study is to substantiate the theoretical and methodological principles and develop practical recommendations for the application of a marketing approach to the management of the formation of a tourist product by tourism enterprises. Management of the formation of a tourist product is one of the leading components in the system of development of a tourist enterprise, because it directly affects the volume of provided tourist services, their quality, completeness in terms of assortment and satisfaction of consumer needs. The income, profit and financial condition of the tourist enterprise directly depend on the success in this area. The key aspects that are in the focus of the marketing product policy during the formation of the tourist product of tourism enterprises are: the range of services; quality and competitiveness of services; price of services; characteristics of the perception of services by their existing and potential consumers and the degree of satisfaction of their needs; provision of additional services, including transfer, insurance, etc.; advertising policy and effectiveness of service promotion; strengthening the positioning of services with the development of one’s own trademark, quality policy in the field of public relations, social responsibility of the enterprise; the intensity and efficiency of innovative activity, in particular in the areas of product, technological and management innovations; successful development and implementation of marketing product strategies. During the formation of the tourist product of the enterprise, such criteria as reliability, accessibility, reputation, safety, understanding of needs, responsiveness of staff, competence, courtesy, communication and tangible factors should be based. The implementation of the strategic marketing system in tourism enterprises, both in general and in relation to the management of the formation of their tourist product, requires appropriate formalization, which should take place taking into account the influence of socio-psychological motives and factors that determine the general direction of consumer behavior of customers. The policy of managing the formation of a tourist product, as well as the development of a tourist enterprise in general, requires the implementation of a complex of organizational and economic measures. Ideally, the formation and implementation of an effective organizational and economic mechanism in this area.